The changes of soil physical and chemical properties of Andisols as affected by drying and rewetting processes - Rahayu, A; Utami, S R; Prijono, S (Brawijaya University, 2015)
Soils from a toposequence in northern slope of Mt. Kawi, Malang were sampled to study the effect of amorphous content on the irreversible drying properties of the soils. Water, clay, organic-C, and available P contents were measured at field capacity (KL), after air-drying for 2 days (K2) , air-drying for 4 days (K4), oven-drying at 40 °C for 1 day (Ko), as well as after rewetting K2 (KL2); K4 (KL4), and Ko (KLo). The results showed that water, clay, organic-C, and available P contents changed after drying and rewetting processes. Drying process decreased clay content but increased available P content. Clay and water content of the rewetted samples, especially after oven-drying (KLo) were lower than at initial field capacity (KL), as indication of irreversible properties. In contrast, available P and organic-C content were higher after drying-rewetting processes. Variation of water, clay, organic-C, and available P contents after drying-rewetting processes were significantly affected by respected properties at initial field capacity. These properties tended to change in accordance to Alo+½Feo content. The effect of Alo+½Feo content, however was statisticaly detected only on the water content at KLo (rewetted after oven-dried) and on organic C content at KL2 and KL4 (rewetted after air-dried for 2 and 4 days).